Influence of the motivational component of the physical education on the students’ training system - Dolynniy, Yuriy
The purpose of the study is to find out the influence of the motivational component on the training system of physical education students who plan to use health-saving technologies in their professional activities in the physical education of schoolchildren who, for health reasons, belong to special medical groups. Professional education of future specialists in physical education and sports in higher education institutions requires technological changes in physical culture and health work with children and youth, who belong to special medical groups due to their state of health. The solution of this direction of training of future specialists in physical education and sports will be more effective if the motivational component of training is applied in the educational process of students. Studies apply the motivational component of learning. Research determines that the use of a motivational component in the training program for future physical education professionals has a much better effect on the learning process of students, mastering the curriculum, self-development, and self-improvement both in higher education and in future professional activities.
Keywords: Physical education